FAKTOR RESIKO YANG MEMPENGARUHI KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL - Anjelina Puspita Sari; Fitriani Fruitasari (Jurnal Sains Kesehatan, 2021)
Antenatal care aims to optimize the mental and physical health of pregnant women so as to reduce the risk of complications of pregnancy and childbirth, the ultimate goal is to reduce maternal mortality and mortality in Indonesia. The purpose of this study to determine the risk factors that affect antenatal care visits to pregnant women. Method This type of research uses observational analytic using cross sectional design. This research was conducted from March to September 2020, with a total sample of 65 respondents. The data were collected by observing retrospective data from the respondents' medical records. The analysis technique uses the Chi-Square test, and The results There was no significant relationship between age and regularity of ANC visits (pv = 0.587), there was a significant relationship between educational status and regularity of ANC visits (pv = 0.013), there was no significant relationship between gravida and regularity of ANC visits (pv = 1,000), there was There is a significant relationship between work status and regular ANC visits (pv = 0.003), there is a significant relationship between husband's support and regular ANC visits (pv = 0.023).